Development of Encyclopedia-Based Natural Disaster Mitigation Teaching Material Supplements in Geography Learning in Senior High School - Erman Syarif (EduLine: Journal of Education and Learning Innovation, 2023)
The objectives of this study are: (1) to develop encyclopedia-based natural disaster mitigation teaching material supplements in geography learning in Senior High School, (2) to measure the level of validity of encyclopedia- based natural disaster mitigation teaching material development in geography learning in Senior High School and (3) to measure the level of practicality of encyclopedia-based natural disaster mitigation teaching material development in geography learning in Senior High School. This research is a type of research and development (R&D). The model used is the ADDIE model with five stages namely analysis, design, development, implementation, and evaluation. The instruments used in this research are product validity and practicality instruments. The results of this study are 1) products that are declared valid based on product validity tests conducted by 3 expert validators namely; learning design experts, material/content experts, and linguists with an average assessment score from the three validators of 4, 74 and are in the valid category, 2) products that are declared practical based on product practicality tests conducted by 14 test subjects namely students in class XII SMA Negeri 3 Takalar and 1 practitioner namely geography subject teacher with a percentage of assessment response of 86%. Thus it can be concluded that the encyclopedia-based natural disaster mitigation teaching materials developed are valid and practical. Natural disaster mitigation teaching materials that have been declared valid and practical can then be used in learning geography in high schools, especially on natural disaster mitigation material.